Application of 18F-FDG PET/CT imaging in a primary angiomatoid fibrous histiocytoma of pulmonary bronchus: case report and literature review - Shao, Mingyan; Fan, Sisi; Qi, Wanling; Luo, Zhehuang; Xu, Rong; Liao, Fengxiang (Frontiers in Medicine, 2024)
Background:Angiomatoid fibrous histiocytoma (AFH) is a clinically rare, low-grade malignant soft tissue tumor that occasionally metastasizes. It accounts for 0.3% of all soft tissue tumors and most frequently occurs in the extremities, followed by the trunk, and the head and neck. Primary angiomatoid fibrous histiocytoma (PAFH) of the pulmonary bronchus is rare. In this paper, the clinical and imaging data of a case of PAFH of the pulmonary bronchus are reported, and the literature is reviewed.Case description:A 57-year-old female patient presented with a six-month history of cough without apparent cause, characterized by paroxysmal dry cough, chest tightness, and shortness of breath, which worsened with activity. She did not experience fever, chills, chest pain, hemoptysis, or night sweats. Laboratory tests revealed an elevated C-reactive protein and ferritin levels, while tumor markers such as AFP, CEA, CA199, CA125, CA50, and T-SPOT were negative. A chest CT scan showed bronchial obstruction, atelectasis, and a soft tissue density in the right middle lobe of the lung. The enhanced scan demonstrated uneven enhancement of endobronchial nodules. An 18F-FDG PET/CT scan revealed a nodular soft tissue density shadow in the right lung bronchus with uneven density, clear boundaries, and increased 18F-FDG uptake, with a maximum standard uptake value (SUVmax) of 11.2. Bronchoscopy revealed a nodular or polypoid mass that was yellow and tough. Based on imaging findings, the preoperative diagnosis favored lung cancer. However, the postoperative pathological diagnosis confirmed primary angiomatoid fibrous histiocytoma (PAFH) of the pulmonary bronchus.Conclusion:The incidence of primary angiomatoid fibrous histiocytoma (PAFH) is very low, and its clinical manifestations and imaging findings lack specificity, with the final diagnosis relying on pathology. PET/CT imaging has a certain value in the diagnosis of PAFH and holds significant application value in preoperative staging, postoperative efficacy evaluation, and follow-up monitoring. In conclusion, this case report further expands the spectrum of lung and bronchial tumors.